Leadership and School Performance through Improving Teacher Quality at SMK Telkom I Medan - Taufiq Ramadhani; Nathanael Sitanggang; Wildansyah Lubis; Rosnelli Rosnelli (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Neglect by the Principal of SMK Telkom I Medan will have an impact on the quality of teachers, thus making teachers will be disrupted in their performance because they only rely on the importance of grades rather than increasing students' ability to understand lessons, which ultimately reduces the ability and competence of teachers. so that later the Principal can make wise decisions that can change the existing work culture, so that teachers are no longer assessment-oriented through outdated learning methods . This research method is a literature research method. The results of the study concluded that SMK Telkom I Medan has a work culture for teachers who always want students to have higher grades, but students of SMK Telkom I Medan do not get the grades as expected, because the idealism and culture that exist in SMK Telkom I Medan are deep-rooted and difficult to change, so action,  policies, as well as solving existing problems must really change the culture and mindset of teachers, so as to be able to change methods, systems and learning models to be more effective and creative, and follow the curriculum made by the Government, namely the Merdeka Belajar curriculum that creates students to think critically, and can analyze problems, as well as learning materials well.